2018
DOI: 10.18632/oncotarget.25468
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of topoisomerase II alpha protein is a factor for poor prognosis in patients with luminal B breast cancer

Abstract: BackgroundThe prognostic value and the best method of testing of topoisomerase II alpha (TOP2A) status have not been established in modern tailored therapy based on breast cancer subtype.ResultsThe frequencies of TOP2A overexpression and TOP2A amplified were 55.8% and 9.5%, respectively. TOP2A overexpression correlated strongly with non-luminal A subtype (χ2-test, p < 0.001). TOP2A overexpression was significantly associated with relapse-free survival in luminal B breast cancer (n = 316; log rank test, p < 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…DNA Topoisomerase II Alpha ( TOP2A ), encoding a DNA topoisomerase, controls topologic states of DNA during transcription. Previous studies reported that overexpression of TOP2A promoted the progression of breast cancer and prostate cancer ( Kirk et al, 2015 ; Shigematsu et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…DNA Topoisomerase II Alpha ( TOP2A ), encoding a DNA topoisomerase, controls topologic states of DNA during transcription. Previous studies reported that overexpression of TOP2A promoted the progression of breast cancer and prostate cancer ( Kirk et al, 2015 ; Shigematsu et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous literature reported that RRM2 promoted tumorigenesis and progression of pancreatic cancer, lung cancer, gastric cancer, ovarian cancer, bladder cancer and other tumors [2124], TOP2A gene encoded a DNA topoisomerase, it is an ATP-dependent synthetase and hydrolase that plays a key role in cells and plays an important role in many cellular biological processes, such as DNA replication, chromatin condensation, chromosome segregation, and chromosome structure retention. Studies have found that high expression of TOP2A promoted the progression of breast cancer [25, 26]. UBE2C is also known as UbcH10, which is a member of the ubiquitin-coupled enzyme E2 family.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly to the observed for ERBB2 , no correlation was found between TOP2α DNA and RNA levels (results in accordance with [51, 52]). In the future, it will be important to quantify TOP2α protein as there are contradictory published works regarding the clinical significance of the TOP2α expression [22, 24, 25, 51, 52].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the gene aberrations, in HBC, the amplification of TOP2α is correlated with the response to anthracycline chemotherapy and a better outcome of the patient’s survival, independently of its protein expression [22, 23]. TOP2α status has several important implications in breast cancer, however standard tools and cut-off values for estimating TOP2α status have not yet been established [24]. In conclusion, the clinical significance of TOP2α in breast cancer has not yet been clarified [22, 24, 25], being a mandatory research area in this field.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation